Performance and Meat Quality of Thin Tailed Sheep in Supplementary Feeding Lemuru Fish Oil Protected By Saponification with Different NaOH Concentration - Setyaningrum, Agustinah; Soeparno, Soeparno; Yusiati, Lies Mira; Koestantinah, Koestantinah (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
This study was aimed to obtain oil and the exact saponification with different NaOH concentration to protect unsaturated fats, which does can result in good production performance and lamb meat quality with low saturated fatty acid. Stage one studied the performance of sheep production on supplementing lemuru fish oil (LFO) protected with different saponification optimization. Twenty lambs aged 5-6 months early weighing 8-14 kg were divided into 4 treatments, namely P0 basal feed (50% elephant grass + 50% concentrate), P1 (basal feed + soap LFO NaOH 10%), P2 (basal feed + soap LFO NaOH 20%) and P3 (basal feed + soap LFO NaOH 30%) with completely randomized design and 5 replication for performance and 3 replication for meat quality. The results showed that the treatment effect was not significant (P>0.05) on the consumption of dry matter (DM), crude protein (CP), ether extract (EE), total digestible nutrien (TDN), daily gain and blood cholesterol. P2 yield the highest daily gain 130.95 Â± 19.29 g/head/day of cholesterol at the same time low of 58.67 mg/dl. Stage two studied the criteria of lamb carcass and meat quality in supplementary feeding LFO protected with different saponification optimization. Twelve sheeps were slaughtered for P0, P1, P2 and P3. The results showed that the treatment effect was not significant (P> 0.05) to slaughter weight, carcass weight and carcass percentage, the physical quality of meat (pH, water holding capacity, cooking losses and tenderness), and chemical quality of the meat (DM levels, CP , EE, saturated fatty acids and unsaturated fatty acids) except in EPA and DHA increased very significantly (P<0.01). Conclusively, giving soap LFO with different optimization did not significantly affect the appearance and quality of sheep meat production, except in EPA and DHA which were significantly increased